Clinical staff perceptions of palliative care-related quality of care, service access, education and training needs and delivery confidence in an acute hospital setting. Issue 4 (30th September 2013) - Frey, Rosemary; Gott, Merryn; Raphael, Deborah; O'Callaghan, Anne; Robinson, Jackie; Boyd, Michal; Laking, George; Manson, Leigh; Snow, Barry
Abstract : Context: Central to appropriate palliative care management in hospital settings is ensuring an adequately trained workforce. In order to achieve optimum palliative care delivery, it is first necessary to create a baseline understanding of the level of palliative care education and support needs among all clinical staff (not just palliative care specialists) within the acute hospital setting. Objectives: The objectives of the study were to explore clinical staff: perceptions concerning the quality of palliative care delivery and support service accessibility, previous experience and education in palliative care delivery, perceptions of their own need for formal palliative care education, confidence in palliative care delivery and the impact of formal palliative care training on perceived confidence. Methods: A purposive sample of clinical staff members (598) in a 710-bed hospital were surveyed regarding their experiences of palliative care delivery and their education needs. Results: On average, the clinical staff rated the quality of care provided to people who die in the hospital as 'good' (x̄=4.17, SD=0.91). Respondents also reported that 19.3% of their time was spent caring for end-of-life patients. However, only 19% of the 598 respondents reported having received formal palliative care training. In contrast, 73.7% answered that they would like formal training. Perceived confidence in palliative care delivery was significantly greater for those clinical staff with formal palliative care training. Conclusions: Formal training in palliative care increases clinical staff perceptions of confidence, which evidence suggests impacts on the quality of palliative care provided to patients. The results of the study should be used to shape the design and delivery of palliative care education programmes within the acute hospital setting to successfully meet the needs of all clinical staff.